Effects of Traditional and Chemical Ripening Methods on the Physicochemical Properties and Microbial Quality of Banana and Pawpaw Fruits - Fakile, Oluwapamilerin; Eviano, Okolosi; Solana, Olorunfunmi; Mercy, Adedokun; Ayo, Oke (Journal of Pure & Applied Sciences, 2025)
This study was conducted to evaluate the effects of traditional and chemical ripening methods on the physicochemical properties and microbial quality of banana and pawpaw fruits. The physicochemical properties and microbial load of the fruits were analyzed using standard analytical and microbiological methods. Unripe banana and pawpaw fruits served as control samples. Naturally ripened bananas had the highest protein (4.63%), fat (1.54%), sugar (9.33%), pH (4.47), and vitamin C (6.16 mg/100 g) contents after 72 hours. In contrast, bananas ripened with calcium carbide exhibited the highest moisture (97.55%), ash (3.00%), fiber (1.67%), carbohydrate (55.16%), and titratable acidity (0.20%) at 72 hours. For pawpaw, the sample placed in an airtight bag had the highest moisture (97.21%) and ash (0.50%) content, whereas the blanched sample had the highest fat (0.13%), carbohydrate (13.33%), and pH (7.77) values. Pawpaw ripened with calcium carbide showed the highest protein (0.96%), titratable acidity (1.20%), and vitamin C (0.98 mg/100 g) contents at 72 hours. Microbial analysis revealed that after 72 hours of ripening, bacterial and fungal isolates were present on the fruit surfaces. The identified bacterial isolates included Pseudomonas spp., Citrobacter spp., Staphylococcus aureus, Enterobacter spp., Micrococcus spp., and Escherichia coli. Fungal isolates included Aspergillus flavus, Aspergillus niger, and Fusarium spp. The results indicate that natural ripening methods, such as open-shelf ripening and airtight bag storage, led to a significant increase in nutrient content compared to chemical ripening with calcium carbide.